The relationship of concentration and eye-hand coordination with accuracy of backhand backspin serve in table tennis - Jeki Haryanto; Frizki Amra (International Journal of Technology, Innovation and Humanities, 2020)
The purpose of this study was to analyze the relationship between concentration and hand eye coordination with the accuracy of backhand backspin service. Quantitative approaches and correlational methods are used in this study. This research was conducted at PTM Gempas. The population in this study were all cadet athletes at PTM Gempas, while the sampling technique used was saturated sampling, which means that all athletes totaling 20 people were used as samples. Player concentration data is collected using a concentration grid test, hand eye coordination data is obtained by throwing a tennis ball test, and data for backhand backspin service accuracy is obtained by testing servicing. The results of this study are as follows: 1) Concentration has a strong enough relationship with the accuracy of backhand backspin service, 2) Hand eye coordination has a strong enough relationship with backhand backspin service accuracy. 3) Concentration and hand eye coordination together have a strong enough relationship with backhand backspin service accuracy. Table tennis coach should train the concentration and eye-hand coordination to improve the athlete's service accuracy.